2014
DOI: 10.1371/journal.pone.0108595
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of DP2 (CRTh2), a Prostaglandin D2 Receptor, in Human Mast Cells

Abstract: PGD2 has long been implicated in allergic diseases. Recent cloning of a second PGD2 receptor, DP2 (also known as CRTh2), led to a greater understanding of the physiological and pathophysiological implications of PGD2. PGD2 signaling through DP1 and DP2 mediates different and often opposite effects in many cell types of the immune system. Although mast cells (MC) are the largest source of PGD2 in the body, there is little information about their potential expression of DP2 and its functional significance. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…PGD 2 also reduced responses to systemic or passive anaphylaxis supporting an important role of this lipid mediator and DP1 in MC function. Human MC and MC lines were shown to express DP2, however, the GPCR was observed mostly intracellularly . In agreement functional studies showed that they were unresponsive to stimulation with agonists.…”
Section: G‐protein‐coupled Receptors (Gpcrs)supporting
confidence: 56%
“…PGD 2 also reduced responses to systemic or passive anaphylaxis supporting an important role of this lipid mediator and DP1 in MC function. Human MC and MC lines were shown to express DP2, however, the GPCR was observed mostly intracellularly . In agreement functional studies showed that they were unresponsive to stimulation with agonists.…”
Section: G‐protein‐coupled Receptors (Gpcrs)supporting
confidence: 56%
“…Whether the enhanced PGD 2 release following activation of human skin mast cells with IgE/antigen and SCF occurs through a similar mechanism is not known. PGD 2 is a ligand for CRTh2, a receptor expressed on most of the cells important for the pathogenesis of allergic diseases such as Th2 CD4 + lymphocytes, eosinophils and basophils, ILC2 cells, and mast cells …”
Section: The Priming Effect Of Stem Cell Factor On Mast Cell Mediatormentioning
confidence: 99%
“…In human nasal polyps, 34% of mast cell express CRTH2 receptor. Additionally, 87% of LAD2 human mast cell line and 98% of primary cultured human mast cell showed expression of intracellular CRTH2 [61]. The expression of CRTH2 receptor has also been noticed on basophils that may be responsible for chemotaxis of these cells at the inflammatory site [41, 62].…”
Section: Vasoactive Intestinal Peptide Receptors Expression On Thementioning
confidence: 99%